A “war” over lobster and whales: The issue-attention cycle, media discourse, and political ecology of right whale science and conservation in six US newspapers - Reamer, Marcus; Macdonald, Catherine; Wester, Julia; Fielding, Russell; Shriver-Rice, Meryl (Frontiers in Communication, 2024)
News media are important and influential actors in environmental politics. Their reporting on social and environmental issues often follows issue-attention cycles (IACs) that emphasize drama and problematization to maintain public interest. This study examined nearly 13 years of news coverage to understand the media discourse about the Critically Endangered North Atlantic right whale (NARW) and its conservation. 356 texts published in six large US newspapers between January 1, 2010 and March 15, 2023 were analyzed using content analysis and critical discourse analysis. NARW conservation and management received increased public attention and an IAC began in 2017 after an Unusual Mortality Event began, with 75 percent of the sampled articles (n = 267) published from 2017 on. The Boston Globe published a majority of the sampled texts (n = 209) and Globe reporter David Abel was the most prolific journalist with 50 bylines. The coverage featured six themes representing threats to the species, science and technological development, and tourism, local lifestyle, and culture. The most common topic was that of American lobster fishing gear and whale entanglements (n = 162, 45.5%). In that discourse journalists emphasized the political ecology of NARW conservation, focusing on disagreements between whale experts and advocates and commercial lobster fishermen and their allies as they sought to influence decision making by the National Marine Fisheries Service. Journalists presented the issue through a conflict frame and each group used distinct discursive strategies in an attempt to shape the discourse and public opinion related to new or stricter regulations for the commercial lobster fishery designed to reduce the risk of entanglement for the NARW. Findings suggest that this IAC related to NARW science and conservation has already moved through at least three of five key stages and will inevitably lose public interest, which has important implications for future communication and advocacy related to NARW conservation. This case study demonstrates the continued importance of media to conservation – as public forums for discussion, essential parts of organizational strategies for change, and as an externality that can influence conservation outcomes. Support for communication research and practice are vital to successful conservation.